Empowering Rural Tourism through BUMDes Innovation: An Exploratory Study in Klaten Regency - El Anshori, Yuli Tirtariandi; Enceng, Enceng (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
The development of ecotourism in Indonesia has increasingly involved Village-Owned Enterprises (BUMDes) as institutional drivers of rural innovation and socio-economic transformation. This study explores the innovation practices of BUMDes in Klaten Regency, Central Java, which hosts one of the highest concentrations of active BUMDes in the country. Using a qualitative descriptive approach, the research examines six villages, including BUMDes classified as advanced, developing, and growing, with a focus on how innovation principles are implemented in ecotourism development. Data were collected through interviews, observations, and document analysis. The findings reveal that successful BUMDes adopt cooperative, participatory, emancipatory, transparent, accountable, and sustainable management practices. Villages such as Ponggok have leveraged natural resources, particularly water-based tourism, to generate substantial local revenue, reduce unemployment, and promote community participation. However, challenges remain, including limited human resources, regulatory constraints, and uneven innovation capacity across BUMDes categories. The study underscores the importance of institutional innovation, capacity building, and cross-sector collaboration in realizing ecotourism’s potential for rural empowerment. These insights contribute to the discourse on sustainable village development and provide practical implications for policy and community-based tourism governance.